Hypothalamic GPCR Signaling Pathways in Cardiometabolic Control - Deng, Yue; Deng, Guorui; Grobe, Justin L.; Cui, Huxing (Frontiers in Physiology, 2021)
Obesity is commonly associated with sympathetic overdrive, which is one of the major risk factors for the development of cardiovascular diseases, such as hypertension and heart failure. Over the past few decades, there has been a growing understanding of molecular mechanisms underlying obesity development with central origin; however, the relative contribution of these molecular changes to the regulation of cardiovascular function remains vague. A variety of G-protein coupled receptors (GPCRs) and their downstream signaling pathways activated in distinct hypothalamic neurons by different metabolic hormones, neuropeptides and monoamine neurotransmitters are crucial not only for the regulation of appetite and metabolic homeostasis but also for the sympathetic control of cardiovascular function. In this review, we will highlight the main GPCRs and associated hypothalamic nuclei that are important for both metabolic homeostasis and cardiovascular function. The potential downstream molecular mediators of these GPCRs will also be discussed.